2009
DOI: 10.1213/ane.0b013e31818e0d34
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous Lidocaine on Brain Activation During Non-Noxious and Acute Noxious Stimulation of the Forepaw: A Functional Magnetic Resonance Imaging Study in the Rat

Abstract: BACKGROUND Lidocaine can alleviate acute as well as chronic neuropathic pain at very low plasma concentrations in humans and laboratory animals. The mechanism(s) underlying lidocaine’s analgesic effect when administered systemically is poorly understood but clearly not related to interruption of peripheral nerve conduction. Other targets for lidocaine’s analgesic action(s) have been suggested, including sodium channels and other receptor sites in the central rather than peripheral nervous system. To our knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Compared with our results, the most striking difference is the involvement of the limbic system in PI perception. Previous brain imaging studies related to neuropathic pain perception have reported the cerebral regions: the thalamus and anterior cingulate cortex (22); the primary somatosensory area (SSp), secondary somatosensory cortex, hippocampus, posterior hypothalamic nucleus, and ventral tegmental area (23); and the parietal cortex, insula, and frontal cortex (24). According to our results, NP-evoked rats by L5 SNL also indicated almost identical regions to those previously reported.…”
Section: Discussionsupporting
confidence: 88%
“…Compared with our results, the most striking difference is the involvement of the limbic system in PI perception. Previous brain imaging studies related to neuropathic pain perception have reported the cerebral regions: the thalamus and anterior cingulate cortex (22); the primary somatosensory area (SSp), secondary somatosensory cortex, hippocampus, posterior hypothalamic nucleus, and ventral tegmental area (23); and the parietal cortex, insula, and frontal cortex (24). According to our results, NP-evoked rats by L5 SNL also indicated almost identical regions to those previously reported.…”
Section: Discussionsupporting
confidence: 88%
“…More contradictory data can be found about the effect of lidocaine in a similar model. In the paper of Luo et al (2009) systemic administration of lidocaine up to 10 mg/kg i.v. had no inhibitory effect on painful train stimuli evoked BOLD responses in the brain, it rather increased the activation.…”
Section: Tablementioning
confidence: 99%
“…Nevertheless, other researchers have made great inroads into this domain using anesthetized preparations for pain stimuli applied to the paw using alpha-chloralose (Tuor et al, 2000;Malisza and Docherty, 2001;Luo et al, 2009) or isoflurane (Asanuma et al, 2008;Governo et al, 2008). Alpha-chloralose is a mild hypnotic drug that does not produce complete anesthesia because of its poor analgesic properties but does not alter metabolic coupling (Ueki et al, 1992).…”
Section: Comparison With Other Fmri Studies Of Pain In Ratsmentioning
confidence: 99%